Waqi-Allah, Muhammad. “Features of Shaykh al-Ghazali’s Political Thought,” Year 2, Issue 7 (Winter 1416 AH/ 1997 CE), Pp. 105-137. - وقيع الله محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1997)
Ijtihad (intellectual reasoning) and tajdīd (renewal) are evident in all of Shaykh Muhammad al-Ghazali’s writings, and his political ijtihad is an extension of the iṣlāḥī (reformist) school of thought that began with Jamal al-Din al-Afghani. Among al-Ghazali’s writings, ten books may be regarded as purely political, and they are considered the appropriate gateway to the emergence of the world of political systems from an Islamic perspective. Muhammad Waqi-Allah’s article begins with an explanation of the comprehensive approach in political science, and the intended meaning of reclaiming authority to religion, shūrā (consultation), and the climate of political deliberation. He discusses the concept of socialism, labor, distribution of wealth, right to work, right to wages, property rights, and addresses nationalism and international relations. His article concludes by capturing al-Ghazali’s position on the political culture of the Muslim Ummah.